Many faces of the right-wing populism. Book review of ‘Right-wing populism: Global trend and regional features’ ed. by L.S. Okuneva, A.I. Tevdoi-Burmuli - M. V. Nozhenko (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The review examines a new collective monograph edited by L.S. Okuneva and A.I. Tevdoi-Burmuli: ‘Right-wing populism: Global trend and regional features’, published in 2020. The reviewer notes that a growing interest in both Russian and foreign academic community towards the phenomenon of populism has been witnessed in recent years. However, scholars still haven’t reached a consensus on the nature and content of this phenomenon, its role in the political systems of individual countries and regions, as well as on prospects for its further development. In this regard the book under review which provides a broad geographical and thematic perspective coverage is of particular relevance. At the same time, the reviewer notes that this very breadth provokes critical comments. For instance, the reviewer points to certain imbalances in the structure of the book, as well as some inconsistencies in the authors’ narratives. The latter may be related to the fact that the authors have widely diﬀering approaches to the nature of populism. As a result, the book under review should be considered as a collection of essays united by a common theme rather than a collective monograph based on a common theoretical and methodological framework. However, this in no way downplays academic contribution of each individual author and the relevance of the book as a whole. The reviewer examines each chapter, brieﬂy presenting the author’s position and the key ﬁndings, and concludes that the book in general contributes signiﬁcantly to the academic study of the right-wing populism and raises new research questions. With regard to the latter, the book highlights both the ambiguity of populism, its immanent connection with modern trends in the development of political systems, and the social and psychological factors that contribute to the growing popularity of populist ideas.